Early recurrence of ischaemic stroke of cardioembolic cause and delayed anticoagulation: a case report - Agnes Aghetti; Peggy Reiner (BioExcel Publishing Ltd, 2022)
Introduction: Anticoagulation therapy is used for the management of atrial fibrillation to prevent new clots from developing. However, neurologists face the challenge of when to initiate/reintroduce treatment after a recent episode of stroke without increasing haemorrhagic risk, especially if the stroke is large and/or complicated with haemorrhagic transformation. Case presentation: This report describes the case of a 72-yearold man who had an ischaemic stroke of the right posterior cerebral artery. The patient had permanent atrial fibrillation, discovered in hospital. He was not on chronic anticoagulation therapy before stroke. His anticoagulation therapy was postponed due to a haemorrhagic lesion, leading to new ischaemic stroke. The patient suddenly had right hemiplegia with aphasia for which a mechanical thrombectomy was performed but complicated by embolization into the left posterior cerebral artery with failure of thromboaspiration of this clot. Finally, the patient presented with intracranial hypertension due to ischaemic lesions and died 3 days after his readmission. Conclusion: When to start anticoagulation therapy after ischaemic stroke is an unresolved question but should be discussed at least twice weekly in a stroke unit based on the clinical evolution of the patient.